Čitalništvo in bralno društvo pri Mali Nedelji (University of Maribor Press, 2022)
The Reading Movement and Reading Society at Mala Nedelja . The monograph presents the establishment of the reading room at Mala Nedelja (1 April 1871). The credit for its establishment goes to the national awakener Anton Božič, who was among the organisers of the national cultural event at Mala Nedelja called Bèsede (1867). He attended (and was a member of the preparatory board of) the first camp on Slovenian soil in Ljutomer (9 August 1868). Educated people and Božič’s compatriots from Mala Nedelja also took part in the founding, e.g., Father Franc Zmazek, Anton Strajnšak, Radoslav Razlag and Alojzij Gregorič, who already sought to establish a library at Mali Nedelja in 1864, while still a student. The premises for the reading room was made available free of charge by Anton Strajnšak, a farmer from Bučkovci. The monograph focuses on the establishment of the reading room at Mala Nedelja, the reading movement in Prlekija, the cultural and political history of the time and the famous people of Prlekija, who in the second half of the 19th century, took steps that promoted national awareness and state-building, placing the mother tongue on the barricades of Slovenia. It is a presentation of the reading movement in Prlekija within the framework of Slovenian history, language (modern Slovene and its state-building role), literature (eg. the national awakening period of the literature of Prlekija), pedagogy (reading rooms and their role in history curriculum) as well as journalism and theatre. The authors of the discussions are Blanka Bošnjak, Anton Božič, Franc Čuš, Stane Granda, Nina Horvat, Jernej Jakelj, Marko Jesenšek, Stanislav Kocutar, Diana Košir, Dragan Potočnik, Miran Puconja and Vlasta Stavbar.